Implementation of a practice model for inpatient psychiatric clinical pharmacist practitioners with prescriptive authority at a veterans health care facility - Chinedu Diokpa, PharmD; Courtney Givens, PharmD (American Association of Psychiatric Pharmacists, 2024)
Clinical pharmacists play a valuable role on collaborative health care teams, especially in the field of mental health. However, there is a need to explore innovative practice models that optimize their potential in providing comprehensive medication management in inpatient psychiatric settings. This report aims to describe the implementation of a practice model using an inpatient psychiatric clinical pharmacist practitioner performing comprehensive medication management. The implementation of a practice model using a psychiatric clinical pharmacist practitioner was a feasible way to deliver comprehensive medication management and other clinical services in an inpatient psychiatric setting amid staffing challenges. Whereas limitations such as resource constraints must be considered, the success of this model highlights the value of a versatile psychiatric clinical pharmacist practitioner. These findings might offer insight to other health care facilities considering a similar approach to provide mental health care through the use of a psychiatric clinical pharmacist practitioner.